Digital Entrepreneurship: Peran Aplikasi Mobile dalam Menciptakan Peluang Bisnis Baru - Aqibul Muttaqin; Akhmad Shohibul Ilman; Laelik Nur Kholissoh; Ferida Rahmawati (Yayasan Al-Afif, 2026)
The rapid growth of mobile applications has changed the way people start and run businesses in Indonesia, yet many studies still focus narrowly on e-commerce platforms without mapping the wider range of opportunities mobile technology creates. This study aims to identify the role of mobile applications in generating new business opportunities within digital entrepreneurship. A qualitative method with a literature study approach was employed, drawing on scientific articles and documents published between 2018 and 2023 from Google Scholar and ResearchGate. The findings show that mobile applications across marketplace, fintech, transportation, and creative categories have given rise to low-capital business models such as dropshipping, affiliate marketing, live-hosting services, and micro digital agencies. These applications also support business actors in payment processing, logistics, and content production. The implication is that mobile technology lowers entry barriers for new entrepreneurs while encouraging more inclusive participation in the digital economy, particularly among groups previously excluded from the formal labor market.